Bubue Karang Enim and the Process of Islamization in the Malay Community of Muara Enim - Jamil, Syahril; Asmara, Muhammad Abdillah; Sarip, Muhamad; Rizki, Syamil; Atih, Rahmah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research shows how the process of Islamization of the Palembang Malay community, especially in the Muara Enim area by examining the Bubue Karang Enim manuscript written by Sheikh Jalaluddin in 1342 Masehi. This research also looks at how the role of the ulama in the spread of Islam in the Muara Enim area which is part of the Palembang Malay community. This research uses a qualitative method with an analytical descriptive approach to the Bubue Karang Enim manuscript as well as through literature studies related to the spread of Islam in the Palembang Malay community. As for the results of this research, it can be seen how the da'wah carried out by Sheikh Jalaluddin, a scholar from Makkah al-Mukaramah, and Sheikh Ja'far Shadiq (Sunan Kudus) who was ordered by Raden Fatah Sultan of Demak, Sheikh Yusuf Ibrahim from Jambi, and Sheikh Ahmad Muhammad were students of Sheikh Jalaluddin, each scholar then had ten students and made ridges then spread the teachings of Islam in various regions such as Bengkulu, Lahata, Bangka, and other areas. This research also shows how the process of spreading Islam by the ulama to the people of Palembang from time to time.